Intake, nutrient utilization and growth performance of lambs fed detoxified Jatropha curcas meal - PATIL, S S; SHARMA, K; DUTTA, NARAYAN; PATTANAIK, A K (The Indian Journal of Animal Sciences, 2017)
The study assessed the effect of dietary supplementation of detoxified Jatropha meal (DJM) on feed intake, nutrient utilization and growth performance of lambs. Growing lambs (24) of similar age and body weight (15.76Â±1.92kg) were selected for this study. The experimental lambs were allocated in four groups i.e. control group (CG) without DJM and replacing soybean meal (SBM) of CG with DJM on iso-nitrogenous basis in treatment groups (TG) by 12.5% (T1), 25% (T2) and 37.5% (T3). The feeding cum growth trial was conducted for a period of 180 days. The intake of dry matter (DM), organic matter (OM) and digestibility coefficients of DM, OM, CP, NDF and ADF were comparable between CG and TGs. Nutrient intake, DCP, TDN, Nitrogen (N) intake, excretion and retention were comparable between CG and TGs. Replacement of SBM with DJM even up to 37.5% did not show any significant impact on urinary excretion of total purine derivatives (PD), creatinine (C) and their ratio. Microbial N synthesis (g/d) and efficiency of microbial N synthesis of CG were comparable irrespective of DJM%. The initial and final body weights (BW) of lambs between CG and TGs were also comparable. Total BW gain (kg), average daily gain (ADG; g d-1) and feed conversion ratio (kg DM/kg gain) by lambs did not differ significantly between CG and TGs. The study concluded that SBM in the diet of lambs could be replaced by DJM up to 37.5% without any adverse impact on nutrient intake, digestibility, rumen microflora and growth of the lambs.